Measurement of the electron charge asymmetry in inclusive W production in pp collisions at sqrt[s]=7 TeV. - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2012)
A measurement of the electron charge asymmetry in inclusive pp→W+X→eν+X production at sqrt[s]=7  TeV is presented based on data recorded by the CMS detector at the LHC and corresponding to an integrated luminosity of 840  pb(-1). The electron charge asymmetry reflects the unequal production of W(+) and W(-) bosons in pp collisions. The electron charge asymmetry is measured in bins of the absolute value of electron pseudorapidity in the range of |η|<2.4. The asymmetry rises from about 0.1 to 0.2 as a function of the pseudorapidity and is measured with a relative precision better than 7%. This measurement provides new stringent constraints for parton distribution functions.